Penentuan Nilai Parameter Gempabumi Menggunakan Metode Geiger dan Hukum Laska pada Pulau Lombok - Sari, Bella Dessy Wulan; Djayus, Djayus; Supriyanto, Supriyanto; Hendrawanto, Benny (GEOSAINS KUTAI BASIN, 2022)
Earthquake is an event of the Earth vibration caused by the shifting of rock layers on Earth immediately that caused by the shifting of tectonic plates. The aim of this study is to know the Earthquake's Parameter. The Earthquake that happened in Lombok, August 5th 2018, at 18:46:37 (Western Indonesian Time), with magnitude 7,0 SR. By using six Earthquake recording stations, there are KLNI (in Mataram), TWSI (in Sumbawa), SRBI (in Buleleng), DNP (in Denpasar), PLAI (in Plampang) and BYJI (in Banyuwangi). The Coordinate of each Earthquake observer station, P Wave and S Wave are included. The Epicenter value is analyzed using the Laska Law and the Hypocenter value is analyzed using the Geiger Method. The results showed the Earthquake Parameter with coordinates; Latitude: - 8.28 South; Longitude: 116,47 East, the Epicenter value of KLNI station is 100 km away, the TWSI station is 150 km away, the SRBI station is 300 km away, the DNP station is 300 km away, the PLAI station is 317 km away, the BYJI station is 483 km away and the hypocenter value is 30 km. Deduced from the depth, this Earthquake included into Shallow Earthquake and included as Main Shock or Main Earthquake.